Atributos de um latossolo sob aplicação de vinhaça e cultivo de cana-de-açúcar - Martins, Maíra de Emílio (2012)
The stillage is an important source of nutrients and organic matter, however, has brought changes in soil properties. Thus, the aim of this study was to evaluate the chemical, physical and microbiological parameters of a soil cultivated with sugar cane and with different time of vinasse application. For the work we chose three study areas: one area that never received vinasse, one that takes six years received vinasse and an area that receives vinasse for 16 years. We evaluated chemical attributes (macro and micronutrients, pH, organic matter, base saturation), physical attributes (resistance to penetration (RSP), texture, moisture, total porosity, macro and microporosity, bulk density (Ds) and aggregate stability) and microbiological (microbial biomass carbon (C- BM), soil basal respiration (SBR), metabolic quotient (qCO2), bacteria, fungi and actinomycetes total viable count, and enzymatic activity of acid phosphatase (AP), basic phosphatase (BP) and β-glucosidase). The data were subjected to analysis of variance Kruskal-Wallis test at 5% probability for these do not show normal distribution, with seven treatments with three replicates for the physical attributes, and three treatments, two periods, and 7 repetitions, for microbiological attributes. The stillage is able to improve the chemical properties of a sandy soil by fertilization maintenance, and increase the content of some soil nutrients, like potassium and phosphorus. Indirectly promotes the positive effects of vinasse on some soil physical properties such as aggregate stability, however, has a low ability to improve the carrying capacity of the soil. It was also found that the stillage is effective in cushioning the effects of dry period in the soil microbial activity, promotes the development of some microbial groups, such as fungi and interferes directly in the explosion of microbial activity in the dry season.